Comprehensive Dental Care for Children with Visual Impairment - Nisrina, Shafiya Fildza; Loebis, Rozalina (Universitas Airlangga, 2024)
Introduction: Children with visual impairment are more susceptible to acquiring pathologies in the oral cavity than the general population, the most prevalent of which are dental caries, inflammation of the gums, and loss of the structures that support the teeth. The oral health care needs of visually impaired children are needed. Purpose: To provide a better understanding that can guide ophthalmologists about the importance of comprehensive dental care for children with visual impairments. Review: Factors that respond to the need for oral health care in visually impaired children are lack of ability to carry out oral hygiene habits, lack of knowledge on the part of health personnel to provide services adapted to the needs of this population, absence of promotion and education programs, and lack of public policies on oral health. This article discusses the dental aspects of visual impairment, its implications for obtaining dental care, associated oral conditions, and medical complications. Conclusion: It is imperative to prioritize the implementation of preventive methods and oral health education among visually impaired children. The function of the dentist is significant in the management of children with such conditions. Ophthalmologists should collaborate with dentists who possess a strong drive to provide care for children with special needs such as visual impairment and will discover that this endeavor offers significant opportunities to be an enriching experience.